Epidemiological investigation and surgical treatment of canine mammary tumors in Dalian, China, from 2019 to 2023 - Jing, Zheng; Feng, Jiawang; Jin, Hongyan (PLOS ONE, 2024)
Objective of this study is to investigate the epidemiological characteristics, clinical features, and treatment outcomes of canine mammary tumors in Dalian, providing insights into prevention and management strategies. A retrospective analysis was conducted on 198 cases of canine mammary tumors diagnosed in outpatient departments across several veterinary hospitals in Dalian. Data on breed, age, sex, tumor location, and clinical staging were collected and correlated with treatment modalities and prognosis. Poodles, Chinese pastoral dogs, and Cocker Spaniels exhibited higher incidence rates. The majority of affected dogs were middle-aged and older females, with unneutered dogs and those with a history of false pregnancies being at the highest risk. Benign tumors were more common in younger dogs, while malignant tumors predominated in older dogs, accounting for 89.9% of the cases. Early surgical intervention significantly improved survival and quality of life. Early detection, prompt surgical treatment, and post-operative follow-up are essential for optimal outcomes in canine mammary tumor management. This study summarizes the impact of early sterilization on tumor development and suggests that preventive measures, such as total ovarian extraction prior to the first estrus, are effective in reducing the incidence of mammary tumors.